Effect of the Location of Dental Mini-Implants on Strain Distribution under Mandibular Kennedy Class I Implant-Retained Removable Partial Dentures - Pimduen Rungsiyakull; Kallaya Kujarearntaworn; Pathawee Khongkhunthian; Michael Swain; Chaiy Rungsiyakull (International Journal of Dentistry)
Purpose. To investigate the effect of minidental implant location on strain distributions transmitted to tooth abutments and dental minidental implants under mandibular distal extension removable partial denture. Materials and Methods. A mandibular Kennedy Class I distal extension model missing teeth 35–37 and 45–47 was constructed. Six dental mini-implants were placed at positions A, B, and C, where position A was 6.5 mm distal to the abutment teeth with 5 mm between each position. Fourteen uniaxial strain gauges were bonded on the model at the region of dental mini-implant and abutment (first premolar). Four groups were designated according to the location of the mini-implants. A load of 150 N and 200 N was applied using an Instron testing machine. Loadings consisted of bilateral and unilateral loading. Comparisons of the mean microstrains among all strain gauges in all situations were analyzed. Results. Variation in mini-implant locations induced local strains in different areas. Strains at the tooth abutment were significantly decreased in the group in which implants were placed mesially. Strains around the mini-implants showed different patterns when loaded with different loading conditions. The group in which implants were placed distally showed the lowest strains compared to other groups. Conclusion. Mesially placed mini-implants showed the lowest strain around abutment teeth, while a distally-placed mini-implants presented the lowest strain around mini-implants themselves. Under favorable biting force, mini-implant is an option to assist mandibular distal extension removable partial denture. Mesially placed mini-implants are recommended when the abutment has periodontally compromised conditions and a distally placed mini-implant when periodontal conditions are stable.